ENVIRONMENTAL MANAGEMENT ACCOUNTING, GREEN TRANSFORMATIONAL LEADERSHIP AND ENVIRONMENTAL PERFORMANCE: EVIDENCE FROM HOTELIERS - Dyang Ramadhanty Irmy; Ruth Samantha Hamzah (Universitas Airlangga, 2025)
This research aims to analyze the impact of the implementation of Environmental Management Accounting (EMA) and Green Transformational Leadership (GTL) on the environmental performance of hotel companies in Palembang, Indonesia. The research was conducted using a descriptive quantitative approach. Data were collected through questionnaires distributed to 36 hotels, resulting in 108 respondents. Data analysis was conducted using SmartPLS (Smart Partial Least Square) software by performing descriptive statistical analysis and multiple linear regression to test the relationships between variables. The analysis results show that EMA and GTL each have a positive and significant impact on the company's environmental performance. EMA allows the company to monitor and improve the efficiency of environmental management, while GTL motivates employees to be more concerned about environmental issues. These findings provide practical recommendations for hotel companies to adopt EMA and implement GTL leadership style as part of their strategy to improve environmental performance. The integration of these two approaches can help companies achieve sustainability goals more effectively. This research is novel as it focuses on the hospitality industry, which has rarely been the subject of study. Additionally, this research combines EMA and GTL analysis to explore their impact on the company's environmental performance.